Sensitivity of children to the frequency of syllables in the Spanish orthographic system - Ferroni, Marina (2020)
This paper analyzes whether children are sensitive to Spanish spelling regularities, that is, whether they store and access high frequency sub-lexical units like syllables. A spelling test was administered to 259 argentine children from 4th through 7th grades. The test included 26 low frequency words containing the syllables /be/, /bi/, /siar/ and /sia/ in both their possible forms (<BE>/<VE>, <BI>/<VI>, <CIAR>/<SIAR> and <CIA>/<SIA>), forms that vary in their frequency levels in the Spanish orthographic system. Results indicate that children are highly sensitive to syllable frequency. This seems to indicate that for transparent orthographies, such as Spanish, learners initially rely on grapheme-phoneme conversion, which leads to the storage of sub-lexical units.